Greening the Virtual Smart City: Accelerating Peer-to-Peer Learning in Urban Agriculture With Virtual Reality Environments - Parikh, Tapan; Egendorf, Sara Perl; Murray, Isaiah; Jamali, Ali; Yee, Bryan; Lin, Sammi; Cooper-Smith, Kendra; Parker, Brendan; Smiley, Koron; Kao-Kniffin, Jenny (Frontiers in Sustainable Cities, 2022)
Urban agriculture is emerging across the United States (U.S.) as a distinct food production system that can help address food security and equity concerns of marginalized, urban communities. While urban farming is accelerating across the nation rapidly, the system of peer-to-peer learning that represents farmer education and training in the U.S. is based on rural agriculture. We describe the development of virtual reality (VR) platforms to support farmer knowledge transfer and innovation that transcend the physical constraints of traditional agricultural extension based on on-farm demonstrations. We feature a VR model representing an organic farm in New York City with details of farm operations, and opportunities to stack educational and training materials along with personal narratives, as part of the virtual farm demonstration. The potential for VR to accelerate innovations in food justice is a critical component of smart cities technologies and should be developed in parallel with modernization efforts with land grant universities and their cooperative extension networks of farmer-to-farmer education and training.